PENGARUH KUALITAS AUDIT, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF DAN KOMPONEN DI BURSA EFEK INDONESIA TAHUN 2013 - 2017 - Setyawan, Budi (AGUSPATI Research Institute, 2020)
Companies are required to be able to increase the profits earned every year so that they can compete and develop according to shareholders' expectations. The bigger the company, the more focused tax planning should be so that in the future the company can minimize the payment of the tax burden that must be paid. Higher profits will automatically increase the tax burden which is the responsibility of the company. However, many companies that are getting bigger have the opportunity to manipulate their financial statements under the pretext of implementing Tax avoidance which is still classified within the legal limits of the applicable tax laws. The purpose of this study is to obtain an in-depth analysis of the Effect of Audit Quality, Firm size, and Profitability in influencing corporate behavior in implementing Tax avoidance, especially automotive and component manufacturing companies in the Indonesia Stock Exchange. This research is a quantitative study using the causality method and using SPSS 24 software for data processing. The results showed Audit Quality, Firm size And Profitability are not significant to Tax Avoidance.